2008
DOI: 10.1115/1.2777187
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Shroud Design for Axial Turbine Aerodynamic Performance

Abstract: This paper presents a comprehensive study of the effect of shroud design in axial turbine aerodynamics. Experimental measurements and numerical simulations have been conducted on three different test cases with identical blade geometry and tip clearances but different shroud designs. The first and second test cases are representative of a full shroud and a nonaxisymmetric partial shroud geometry while the third test case uses an optimized partial shroud. Partial shrouds are sometimes used in industrial applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Therefore, the discussion in this investigation is limited to the results obtained from steady-state simulations. Based on the consideration of steady-state calculations, 'Stage' interface (mixing plane approach) was used; 33,42,43 here, the circumferentially average flow information is transferred from the upstream side of the interface to the downstream side, that is, meridional variation of the flow is maintained across the interface. However, the stage averaging at the interface incurs a one-time mixing loss, and this loss is equivalent to assuming that the physical mixing supplied by the relative motion between stator and rotor domains is sufficiently large to cause any upstream velocity profile to mix out prior to entering the downstream blade row.…”
Section: Numerical Techniquementioning
confidence: 99%
“…Therefore, the discussion in this investigation is limited to the results obtained from steady-state simulations. Based on the consideration of steady-state calculations, 'Stage' interface (mixing plane approach) was used; 33,42,43 here, the circumferentially average flow information is transferred from the upstream side of the interface to the downstream side, that is, meridional variation of the flow is maintained across the interface. However, the stage averaging at the interface incurs a one-time mixing loss, and this loss is equivalent to assuming that the physical mixing supplied by the relative motion between stator and rotor domains is sufficiently large to cause any upstream velocity profile to mix out prior to entering the downstream blade row.…”
Section: Numerical Techniquementioning
confidence: 99%
“…One way to seal the blade tip is to interconnect the blades using a shroud. 7,8 However, this method increases the blades weight and centrifugal loading. Hence there is a strong motivation to use unshrouded turbine blades with no interconnection between the blades but in the presence of the so-called leakage flows over the blades tip surface.…”
Section: Introductionmentioning
confidence: 99%
“…Harvey 9 designed a partial shroud structure with winglets for the high-pressure turbine, which can significantly reduce blade cooling requirements and tip leakage loss. Porreca et al, [10][11][12] Rebholz et al, 13 and Liu 14,15 studied shroud reduction on the turbine blade, by comparing the influences of full and partial shroud structure on leakage flow and turbine performance, improved and optimized partial shroud structures were brought up. Li 16 applied four configurations with or without labyrinth seal arranged on casing and rotor blade tip for computational simulations and found that the double-side labyrinth seal achieved the highest turbine stage efficiency.…”
Section: Introductionmentioning
confidence: 99%